2016
DOI: 10.1016/j.biortech.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Potential enhancement of direct interspecies electron transfer for syntrophic metabolism of propionate and butyrate with biochar in up-flow anaerobic sludge blanket reactors

Abstract: Promoting direct interspecies electron transfer (DIET) to enhance syntrophic metabolism may be a strategy for accelerating the conversion of organic wastes to methane, but microorganisms capable of metabolizing propionate and butyrate via DIET under methanogenic conditions have yet to be identified. In an attempt to establish methanogenic communities metabolizing propionate or butyrate with DIET, enrichments were initiated with up-flow anaerobic sludge blanket (UASB), similar to those that were previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(83 citation statements)
references
References 32 publications
1
81
0
1
Order By: Relevance
“…Interestingly, it appears that conductive materials, including graphite particles (Kato et al ., ; Zhao et al ., ), granular activated carbon (Liu et al ., ; Rotaru et al ., ; Xu et al ., ; Dang et al ., ; Lee et al ., ), biochar (Chen et al ., ; Zhao et al ., ), graphene (Tian et al ., ), carbon nanotubes (CNT) (Li et al ., ; Zhang and Lu, ), carbon felt (Xu et al ., ) and carbon cloth (Chen et al ., ; Zhao et al ., ; Lei et al ., ), but also iron oxides as magnetite (Kato et al ., ; Cruz Viggi et al ., ; Baek et al ., ; Zhuang et al ., ; Yamada et al ., ; Tang et al ., ; Yang et al ., ; Yin et al ., ; Zhang and Lu, ; Jing et al ., ) may increase the rate of electron transfer and may affect metabolic pathways in anaerobic microbial processes by promoting DIET, between bacteria and methanogens. In general, these materials are highly stable, have large surface area, good adsorption capacity and high electric conductivity (Figueiredo et al ., ; Van der Zee and Cervantes, ; Pereira et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it appears that conductive materials, including graphite particles (Kato et al ., ; Zhao et al ., ), granular activated carbon (Liu et al ., ; Rotaru et al ., ; Xu et al ., ; Dang et al ., ; Lee et al ., ), biochar (Chen et al ., ; Zhao et al ., ), graphene (Tian et al ., ), carbon nanotubes (CNT) (Li et al ., ; Zhang and Lu, ), carbon felt (Xu et al ., ) and carbon cloth (Chen et al ., ; Zhao et al ., ; Lei et al ., ), but also iron oxides as magnetite (Kato et al ., ; Cruz Viggi et al ., ; Baek et al ., ; Zhuang et al ., ; Yamada et al ., ; Tang et al ., ; Yang et al ., ; Yin et al ., ; Zhang and Lu, ; Jing et al ., ) may increase the rate of electron transfer and may affect metabolic pathways in anaerobic microbial processes by promoting DIET, between bacteria and methanogens. In general, these materials are highly stable, have large surface area, good adsorption capacity and high electric conductivity (Figueiredo et al ., ; Van der Zee and Cervantes, ; Pereira et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in relative abundance of families between control setups and biochar amendments could explain the shift of the microbial community compositions in both the ferrihydrite enrichments ( Figure 4 ). This was expected since biochar has also been demonstrated to enrich iron(III)-reducing bacteria in sludge, wastewater, and soils (Tong et al, 2014; Zhao et al, 2016). The Geobacteraceae family is well known for the ability to utilize acetate as an electron donor for the reduction of Fe(III) (Röling, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…The high iron(III) containing culture environments led to a high relative abundance of iron(III)-reducing bacteria, which was likely outcompete the methanogens for the acetate ( Figures 1 – 4 ). The increase in the relative abundance of iron(III)-reducing bacteria and methanogens ( Figures 1 – 4 ) by natural humic acid and application of biochar, especially the small particle size of biochar, may enhance the interaction between these two kinds of microbes (Tong et al, 2014; Zhao et al, 2016). Additionally, cooperation is necessary between the iron(III)-reducing microorganisms and methanogens.…”
Section: Discussionmentioning
confidence: 99%
“…This result supported the fact that the major reason for the improved performance was the conductivity of the material and not the biomass retention. Zhao et al [66] reported the enhancement in methane production (16-25% increase compared to the control) from propionate and butyrate in the UASB with biochar amendment. A significant enrichment of Geobacter and Methanosaeta species compared to the control reactor suggested that the degradation of the organic acid was promoted by the biochar-mediated DIET.…”
Section: Biochar and Activated Carbonmentioning
confidence: 99%